Antidiabetic activity of of green tea ethanol extract on white mouse - Rohdiana, Dadan; Firmansyah, Adang; Setiawati, Anik; Yunita, Nuni (Research Institute for Tea and Cinchona, 2012)
In China, India, United State, and some small other countries, tea has been consumed to prevent various disease, such as diabetes mellitus. A number of recent research revealed that consumption of green tea has an impact on the ability of insulin sensitivity in reducing glucose content in human body. Research to know antidiabetic activity of ethanol extract of green tea on experimental rats has been conducted using glucose tolerance method on rats. Results showed that application of 720 mg/kg BW of ethanol extract of green tea at 120, 180, and 240 minutes after application could reduce glucose content in the body. While applications of 180 mg/kg BW and 360 mg/kg BW of ethanol extract of green tea reduced glucose content of the body at 180 and 240 minutes after application respectively.